2014
DOI: 10.4049/jimmunol.1301931
|View full text |Cite
|
Sign up to set email alerts
|

Zhankuic Acid A Isolated from Taiwanofungus camphoratus Is a Novel Selective TLR4/MD-2 Antagonist with Anti-Inflammatory Properties

Abstract: TLR4, a membrane receptor that functions in complex with its accessory protein myeloid differentiation factor-2 (MD-2), is a therapeutic target for bacterial infections. Taiwanofungus camphoratus is highly valued as a medicinal mushroom for cancer, hypertension, and inflammation in traditional medicine. Zhankuic acid A (ZAA) is the major pharmacologically active compound of T. camphoratus. The mechanism of action of T. camphoratus or ZAA has not been fully elucidated. We analyzed the structure of human TLR4/MD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…The anti-inflammatory activities of crude extracts of medicinal mushrooms have been demonstrated in previous studies using [ 3 4 5 6 7 ]. Recently, considerable efforts have been focused on the isolation of single compounds with potent and unique biological activities [ 8 9 10 11 ]. Fomes formetarius is a bracket fungus commonly known as horse's hoof fungus, which has been used as a traditional medicine in China and Korea for centuries to treat various disease conditions including cancers and disorders of the gastrointestinal tract [ 12 ].…”
mentioning
confidence: 99%
“…The anti-inflammatory activities of crude extracts of medicinal mushrooms have been demonstrated in previous studies using [ 3 4 5 6 7 ]. Recently, considerable efforts have been focused on the isolation of single compounds with potent and unique biological activities [ 8 9 10 11 ]. Fomes formetarius is a bracket fungus commonly known as horse's hoof fungus, which has been used as a traditional medicine in China and Korea for centuries to treat various disease conditions including cancers and disorders of the gastrointestinal tract [ 12 ].…”
mentioning
confidence: 99%
“…Therefore, both the TLR4/MD-2 and JAK2 activation play a role in LPS induced endotoxemia. Modeling approaches indicate the interaction between ZAA and TLR4/MD2 is a highly hydrophobic recognition, which is confirmed by Native PAGE assay [40]. ZAA also interacts with JH1 domain of JAK2 by three H-bonds and several hydrophobic interactions according to HotLig prediction, which evidenced by Native PAGE assay and immunoblotting.…”
Section: Discussionmentioning
confidence: 85%
“…ZAA also belongs to this type of small molecule triterpenoid drugs. A previous study has demonstrated that ZAA is an LPS antagonist of NF-kB activation in response to inflammatory stimuli [40]. Whether the suppression of STAT3 by ZAA is associated with its observed inhibitory effects on NF-kB pathway needs further investigation.…”
Section: Discussionmentioning
confidence: 97%
“…In addition, our results showed that the combination of Zhankuic acid compounds with chemotherapeutic drugs could also enhance the cytotoxicity in drug-sensitive cell line HeLaS3, indicating there are other molecular mechanisms for cytotoxicity. ZA-A was reported to have anti-inflammatory functions such as the inhibition of ROS produced by fMLF-or PMA-activated peripheral human neutrophils [29], or modulating the production of NO, iNOS, COX2, TNF-α and IL-6, in macrophages [30]. The relationship between anti-inflammation and the cytotoxic effects of ZA-A deserves further experiment investigation to understand the diverse pharmacological roles of ZA-A.…”
Section: Discussionmentioning
confidence: 99%